Obesity and anxiety prevalence on nursery employment (Jóvenes en la Ciencia, 2024)
Nurses face a variety of challenges in their work, from long work hours to exposure to emotionally harrowing situations. The objective of this research was to evaluate the prevalence of anxiety and obesity in nursing staff. Cross-sectional and retrospective descriptive study. A sample of 30 participants was used at convenience, men and women of various ages, graduates, with a technical degree or with a specialty in nursing. The Beck anxiety test was applied along with questions from the article "Development of a questionnaire for the assessment and quantification of lifestyle habits related to overweight and obesity." It was shown that there is a prevalence of anxiety and obesity in nursing staff upon discharge due to sedentary lifestyle and work overload. These results suggest that work activities can promote the presence of anxiety and obesity in nursing staff.